Physicochemical properties of low transition temperature mixtures in water - Yiin, C.L. (Italian Association of Chemical Engineering - AIDIC, 2015)
A new generation of designer solvents, low transition temperature mixtures (LTTMs) could be the ideal solvent for the separation of the main biopolymers in lignocellulosic biomass such as lignin, cellulose and hemicellulose. The separated biopolymers have prospective to be converted into high valuable products. LTTMs can be synthesized from two natural high melting point materials through hydrogen bonding interactions. The objective of this research was to study the effects of water in the physicochemical properties of LTTMs such as hydrogen bonding, thermal stability and lignin solubility. LTTMs were prepared in the presence and absence of distilled water with malic acid as the hydrogen bond donor (HBD) and sucrose as hydrogen bond acceptor (HBA). The molar ratio of malic acid to sucrose was fixed at 1:1. Based on the fourier transform infrared spectroscopy (FTIR) analysis, the FT-IR spectra of all the LTTMs shown representative peak of carboxylic acid group of malic acid turned broader at 1,710 cm-1 for the C=O group. Nevertheless, the peaks involved in the H-bonding due to the formation of LTTMs shifted and became broader within 2,500-3,600 cm-1 for the OH groups of carboxylic acid and alcohols in the presence of water. The degradation temperature of LTTM was not affected by the addition of water which remained at 400 K. In addition, the LTTM with water had increased the lignin solubility from 6.22 to 6.38 wt without affecting the thermal behaviour of LTTMs. Copyright Â© 2015, AIDIC Servizi S.r.l.,.